2019
DOI: 10.3390/coatings9110750
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of a Ni–P–TiO2/Ti3C2Tx Coating with In Situ Grown Nanoparticles TiO2 on Ti3C2Tx Sheets

Abstract: Protective coatings have received considerable attention for the surface treatment of devices. Herein, in situ grown nanoparticles, TiO2 on Ti3C2Tx sheets (TiO2/Ti3C2Tx), are prepared by a simple hydrothermal oxidation method possessing the layer structure, which is applied to prepare protective coatings. The Ni–P–TiO2/Ti3C2Tx coating is prepared by electroplating technology, revealing more excellent properties than those of the Ni–P coating. Compared with the Ni–P coating, even though the Ni–P–TiO2/Ti3C2Tx co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…4(c) ), which represent C–Ti–O x , C–C, and C–O bonds, respectively. 33,34 This result further supports the presence of surface functional groups. From the fact that the C–O bond is not observed in pure ML-Ti 3 C 2 T x MXene (see Fig.…”
Section: Resultssupporting
confidence: 65%
“…4(c) ), which represent C–Ti–O x , C–C, and C–O bonds, respectively. 33,34 This result further supports the presence of surface functional groups. From the fact that the C–O bond is not observed in pure ML-Ti 3 C 2 T x MXene (see Fig.…”
Section: Resultssupporting
confidence: 65%
“…Furthermore, other Ti peaks related to the Ti-C, Ti-X and Ti x O y can be observed in the titanium spectrum. 33 These results demonstrated that Ti 3 C 2 T x is partially oxidized during the hydrothermal synthesis and calcination process. The TiO 2 formation in the layered structure of Ti 3 C 2 T x leads to improved charge transfer and boosts the electrocatalyst properties of the SeCF-MMO/SgCN:MX sample.…”
Section: Resultsmentioning
confidence: 73%
“…In Figure 2e, the TEM image of m-TC40 shows a stacked multilayer microstructure, and the interlayer open channels can be easily visible. The high-resolution TEM (HRTEM) image of m-TC40 in Figure 2f exhibits a crystalline structure with an interplanar spacing of 0.24 nm, which corresponds to the (103) lattice plane, 34 which was also observed from the XRD pattern of m-TC40. Besides, elemental mapping in Figure 2g− k confirms the distribution of Ti, C, F, and O elements present in m-TC40.…”
Section: Morphological Studiesmentioning
confidence: 63%